The Level of Knowledge of Futsal Extracurricular Students at SMP Negeri 5 Binjai Toward Futsal Sports Facilities - Ginting, Reza Agita Gurah; Munawar, Ahmad Al; Sary, Dewi Maya (Educational Sciences Journal, 2025)
This study aims to analyze the level of knowledge of futsal extracurricular students at SMP Negeri 5 Binjai regarding futsal sports facilities. The research employed a quantitative descriptive approach through a survey using a closed-ended questionnaire consisting of 16 items. The total population and sample were 15 students selected through total sampling. Data were analyzed using a proportion formula to determine the percentage of knowledge categories. The findings revealed that students’ knowledge of futsal facility indicators (facilities) reached 53.33%, categorized as moderate, while their understanding of infrastructure indicators was 47.41%, categorized as low. These results indicate that most students possess a limited understanding of standard futsal facilities, both in terms of equipment and supporting infrastructure. The study emphasizes the importance of improving students’ awareness and knowledge of futsal standards to enhance safety, performance, and engagement in extracurricular sports activities. Furthermore, the findings serve as a reference for schools to optimize the quality and safety of sports facilities used in extracurricular programs.